Impact of the food rescue program in commercially discards carried out by community soup kitchens in the agricultural fields of the Lurín Valley. - Santandreu, A.; Siura, S.; Huaman, J.; López, D.; Gómez, A.; Pradel, W.; Fonseca, C.; Juarez, H. (2024)
The food rescue initiative in the Lurín Valley addresses critical global challenges such as food insecurity and waste, focusing on commercial discards from agricultural fields. This pilot project, involving a rescue brigade formed by members of the Pachacamac Community Soup Kitchens Network (REDOPA), was implemented in collaboration with multiple stakeholders. It assessed the economic, nutritional, and environmental potential of food rescue and its implications for public policy. Key results highlight that over eight rescue sessions, 7,482.7 kilograms of fresh produce were salvaged, including sweet potatoes, celery, cabbage, and spinach, benefiting 24 community kitchens and providing over 5,500 meals. The initiative mitigated food waste, enhanced nutritional diversity in community kitchens, and saved participating farmers on labor costs. Nutritional evaluations revealed substantial contributions to energy, vitamins, minerals such as iron, and fiber, supporting the diets of vulnerable populations. The study demonstrated that food rescue initiatives can enhance community resilience, reduce agricultural losses, and strengthen local food systems. Challenges remain in sustaining these efforts, advocating for enabling policies, and improving coordination among producers, community kitchens, and local authorities. The findings underscore the need for continued advocacy and the potential for scaling this model to address systemic food insecurity.